2017
DOI: 10.1111/mec.14158
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection on MHC IIβ in parapatric lake and stream stickleback: Balancing, divergent, both or neither?

Abstract: Major histocompatibility complex (MHC) genes encode proteins that play a central role in vertebrates' adaptive immunity to parasites. MHC loci are among the most polymorphic in vertebrates' genomes, inspiring many studies to identify evolutionary processes driving MHC polymorphism within populations and divergence between populations. Leading hypotheses include balancing selection favouring rare alleles within populations, and spatially divergent selection. These hypotheses do not always produce diagnosably di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 72 publications
1
45
0
Order By: Relevance
“…Both of these GO groups have known functions in parasite defence and have been previously implicated in the response to selection and parasite prevalence in stickleback (Bolnick & Stutz, ; Eizaguirre, Lenz, Kalbe, & Milinski, ; Lohman et al., In review). Previous studies revealed that Roberts Lake and Stream stickleback populations harbour significantly different parasite communities (Bolnick & Stutz, ), with corresponding differences in MHC Class II allele frequencies (Stutz & Bolnick, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both of these GO groups have known functions in parasite defence and have been previously implicated in the response to selection and parasite prevalence in stickleback (Bolnick & Stutz, ; Eizaguirre, Lenz, Kalbe, & Milinski, ; Lohman et al., In review). Previous studies revealed that Roberts Lake and Stream stickleback populations harbour significantly different parasite communities (Bolnick & Stutz, ), with corresponding differences in MHC Class II allele frequencies (Stutz & Bolnick, ).…”
Section: Resultsmentioning
confidence: 99%
“…MHC IIb was sequenced and data were analysed as described in Stutz and Bolnick (). A previous clinal survey of stickleback from this lake and stream revealed population differences in MHC IIb allele frequencies and significant associations between MHC alleles and the prevalence of particular parasites (Stutz & Bolnick, ). The lake–stream transplant experiment revealed that transplanted foreign fish accumulated higher parasite infections than native fish, but parasites apparently exploited native MHC genotypes (Bolnick & Stutz, ; Stutz & Bolnick, ).…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations